BHIMA BHOI: VOICE OF THE VOICELESS AND POET OF THE VOID - Nayak, Nisikanta; Mohanty, Kamal Prasad; Tripathy, Sishir Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Mystic poet-philosopher and greatest of disciples of Mahima Swami, Bhima Bhoi (c. 1850 1895) holds a truly remarkable position in the socio-religious history of Odisha and India. Coming as he did into a marginalized tribal background, his literary voice is the spiritual voice of the Mahima Dharma, which was a radical religion that opposed caste hierarchy and ritual orthodoxy and social alienation. By his deeply spiritual and socially committed poetry Bhima Bhoi appealed to Sunya Brahma, the unmarked Absolute, not only as metaphysical fact, but also as ethical necessity. This paper discusses how Bhima Bhoi has become the voice of the voiceless, the poet of cosmic nothingness and ethical cravings, and a seer whose words give life to justice and dignity movements.